Inggris - Setianingrum , Diah Ayu; Setiawan, Budi; Cahyani, Putri Dwi (JURNAL MANAJEMEN MOTIVASI, 2026)
This study explores how Parasocial Relationships with influencer Fadil Jaidi affect purchase decisions for Head & Shoulders, mediated by brand credibility and word of mouth. Using a quantitative approach, data from 209 respondents were analyzed via PLS-SEM. Findings reveal Parasocial Relationships significantly influence brand credibility, word of mouth, and purchase decisions. Both mediators also positively affect purchase decisions. These results suggest that influencer closeness fosters trust and positive brand communication. Head & Shoulders should consider engaging relaxed yet authoritative influencers and implement reward-based promotions to boost word-of-mouth engagement and consumer trust.